Factors influencing home blood pressure monitor ownership in a large clinical trial - Anbarasan, Thineskrishna; Rogers, Amy; Rorie, David A; Grieve, J W Kerr; Flynn, Robert W V; MacDonald, Thomas M; Mackenzie, Isla S (Journal of human hypertension, 2022)
Home blood pressure monitor (HBPM) ownership prevalence and the factors that influence it are unclear. This study aimed to investigate factors associated with HBPM ownership among participants in the Treatment in Morning versus Evening (TIME) hypertension study. This study is a sub-analysis of the TIME study, a randomised trial investigating the effect of day-time versus night-time dosing of antihypertensive medication on cardiovascular outcomes in adults with hypertension. As part of the TIME study online registration process, participants were asked to indicate whether they owned an HBPM. A multivariable logistic regression model was constructed to determine factors associated with HBPM ownership. Of 21,104 randomised participants, 11,434 (54.2%) reported owning an HBPM. The mean age of all participants at enrolment was 67.7 ± 9.3 years, 12,134 (57.5%) were male, and 8892 (42.1%) reported a current or previous history of smoking. Factors associated with an increased likelihood of reporting HBPM owned include being male (OR:1.47; 95% CI 1.39-1.56) or residing in a less deprived socioeconomic region (IMD Decile 6-10) (OR:1.31; 95% CI 1.23-1.40). Participants with a history of diabetes mellitus (OR:0.74; 95% CI:0.64-0.86) or current smokers, compared to non-smokers, (OR:0.71; 95% CI:0.62-0.82) were less likely to report owning an HBPM. This study has identified important patient factors influencing HBPM ownership. Further qualitative research would be valuable to identify and explore potential patient-level barriers to engagement with self-monitoring of blood pressure.